Peningkatan pemahaman pegawai PT. Semen Baturaja cabang Palembang tentang demensia dan pengenalan metode deteksi penurunan fungsi kognitif pada anggota keluarga - Nindela, Rini; Harun, Yusril; Marisidina, Selly; Handayani, Sri (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2021)
Dementia is a decrease in cognitive function which is quite severe compared to before, so that it interferes with social and professional activities in daily living. Complaints of cognitive decline are often not recognized by the patients themselves. They are often recognized as part of the normal aging process and not sufficient reason to seek treatment. This community service activity in the form of an online seminar aims to provide education to the community about cognitive function and dementia and how to detect it in family members or closest people. The target of this activity is the employees of PT. Semen Baturaja aged 30-50 years as many as 28 people. Evaluation of this activity is carried out by asking participants to fill in a list of questions before and after the seminar via Google Form. Data regarding the level of understanding of the participants is presented descriptively in the form of a diagram. After participating in this activity the participants became more aware that dementia is not a normal condition but a disease that needs to be examined and treated by a doctor. Thus, it can be concluded that this activity is quite effective in increasing public understanding and attitudes about dementia.